A novel GATA6 mutation in patients with tetralogy of Fallot or atrial septal defect - Lin, Xiaoping; Huo, Zhaoxia; Liu, Xingyuan; Zhang, Yangyang; Li, Li; Zhao, Hong; Yan, Biao; Liu, Ying; Yang, Yiqing; Chen, Yi-Han (Journal of human genetics, 2010)
GATA6 is a member of the GATA family of transcription factors, and its expression and functions overlap with those of GATA4 during heart development. Mutations in GATA4 have been related to human congenital heart diseases (CHDs) in several studies, whereas mutations in GATA6 have only recently been reported in patients with persistent truncus arteriosus. Animal experiments have revealed critical roles for GATA6 in the development of the myocardium and cardiac morphogenesis, thereby highlighting the potential involvement of GATA6 defects in the pathogenesis of CHDs. Here, we screened the GATA6 in 270 individuals with sporadic CHDs by direct sequencing. After identification of the mutation, a luciferase reporter assay and real-time quantitative polymerase chain reaction were performed to detect functional changes in the mutant transcription factor. The same heterozygous missense mutation (Ser184Asn) was identified in three patients, including one with tetralogy of Fallot and two with atrial septal defects. This mutation was not found in 500 unrelated ethnically matched healthy subjects. Direct sequencing of this region in the parents of these three patients revealed the same mutation in one of the parents for each patient, and one of the parent carriers presented with a bicuspid aortic valve. Biological analysis revealed clearly decreased transcriptional activity of GATA6 Ser184Asn in vitro . All these data suggest that GATA6 Ser184Asn is a novel mutation associated with CHDs and has an important role in disease pathogenesis.